Approaching Ottoman history an introduction to the sources - Faroqhi, Suraiya 1941- (Cambridge University Press, 1999)
Suraiya Faroqhi's scholarly contribution to the field of Ottoman history has been prodigious. Her latest book represents a summation of that scholarship, an introduction to the state-of-the-art in Ottoman history. In a compelling exploration of the ways that primary and secondary sources can be used to interpret history, the author reaches out to students and researchers in the field and in related disciplines to familiarise them with these documents. By considering both archival and narrative sources, she explains why they were prepared, encouraging her readers to adopt a critical approach to their findings, and disabusing them of the notion that everything recorded in official documents is necessarily true! While the book is essentially a guide to a complex discipline for those about to embark upon their research, the experienced Ottomanist will find much that is original and provocative in its sophisticated interpretation of the field